Um estudo de metamaterial em antenas de microfita - Sousa Neto, Marinaldo Pinheiro de (2014)
Metamaterials have attracted a great attention in recent years mostly due to their electromagnetic properties not found in nature. Since metamaterials began to be synthesized by the insertion of artificially manufactured inclusions in a medium specified host , it provides the researcher a broad collection of independent parameters such as the electromagnetic properties of the material host. In this work was presents an investigation of the unique properties of Split Ring Resonators and compounds metamaterials was performed. We presents a theoretical and numerical analysis , using the full-wave formalism by applying the Transverse Transmission Line - LTT method for the radiation characteristics of a rectangular microstrip antenna using metamaterial substrate, as is successfully demonstrated the practical use of these structures in antennas. We experimentally confirmed that composite metamaterial can improved the performance of the structures considered in this thesis